Recognition and Management of Colonic Perforation following Endoscopy - Thompson, Earl V.; Snyder, Jonathan R. (Clinics in Colon and Rectal Surgery, 2019)
Although rare, perforation can be a devastating complication of colonoscopy. Incidence ranges from 0.012 to 0.65% during diagnostic procedures and is higher in therapeutic procedures. Early diagnosis and management are of paramount importance to decrease morbidity. Diagnostic imaging after colonoscopy can reveal extraintestinal air, but overall clinical status including leukocytosis, fever, pain, and peritonitis is equally important to determine management. With the expanding availability of complex endoscopic interventions, an increasing number of perforations are recognized during colonoscopy or immediately afterward based on high degree of suspicion. Colonoscopic management of these early perforations may be feasible and avoid the morbidity of surgery. Patients who require surgery may be managed with laparoscopic or open surgical techniques. Surgical management may consist of primary repair of the injury, resection with anastomosis, or resection with ostomy. Mechanical bowel preparation before endoscopy decreases fecal contamination after perforation, often obviating the need for ostomy creation.
Keywords: colonoscopy; perforation; colon perforation